Influence of standardized patient body habitus on undergraduate student performance in an Objective Structured Clinical Examination. (March 2014) - Yazbeck-Karam, Vanda; Aoun Bahous, Sola; Faour, Wissam; Khairallah, Maya; Asmar, Nadia
<x xml:space="preserve">Abstract</x> Purpose: Previous studies have shown that the standardized patient's (SP) gender may affect student performance in an Objective Structured Clinical Examination (OSCE). The aim of this study is to investigate the influence of the SPs' body habitus on students' performance in an OSCE counseling station. Methods: Four equally trained female SPs, with either a normal or an obese BMI participated in an OSCE counseling station for cardiovascular risk factors. Ninety-two, second year medical students were randomly assigned to one of the SPs. Station scores were compared and student behavior and opinion regarding the influence of their SP's body habitus on their performance was assessed. Results: There was no difference in mean exam scores for students interacting with SPs with a normal BMI versus increased BMI (14.9 ± 2.2 versus 14.01 ± 2.2/20 respectively, p = 0.06). Additionally, almost all students gave advice about healthy diets (93.5% versus 95.7%) with no specificity regarding the BMI of the SP. Conclusions: The body habitus of the SP did not significantly affect students' performance in an undergraduate OSCE about cardiovascular risk factors, suggesting that students at that level may primarily focus on gaining points the diagnostic checklist without considering SPs as real patients.